The House at Pooh Corner - Milne, A A (Egmont Children's Books Ltd, 1989)
This Pooh and Piglet Book is a complete chapter fromThe House at Pooh Cornerby A.A. Milne and features Pooh and his friends.
Keywords: Juvenile literature-Fiction